Experimental evaluation on mechanical performance of OSB webbed parallel strand bamboo I-joist with holes in the web. (30th December 2015) - Chen, Guo; Li, Hai-tao; Zhou, Tao; Li, Cheng-long; Song, Yu-qi; Xu, Rui
Highlights: Effect of the holes in the web on the OSB webbed parallel strand bamboo I-joists was investigated. The hole height limit for the joists with no obvious strength reduction effect was proposed. The paper addresses the problem of critical clear distance between the two holes in the web. Abstract: Holes are often made in the web of the OSB webbed bamboo I-joists for the passage of plumbing lines and ventilation systems. A comprehensive study was conducted in order to determine effect of the parameters, such as the size, shape and clear distance of the holes, on the behavior of the joists. A total of 92 OSB webbed bamboo joists were tested to failure to investigate the failure modes and failure mechanism of them. The results showed that holes in the web have considerable effect on the strength reductions of specimens. Holes sharply changes the stress state and reduces the strength evidently due to the high shear stresses appearing in the vicinity of the hole. With the increase of ratio of the hole size to web height, the peak load capacity and stiffness of the joists with holes decreased significantly. A web hole with sharp corners caused greater stress concentrations than the circular hole. Results from the tests on I shaped joists with two circular and two square web holes with a size of 50% web depth showed that the critical clear distance is about 2 times and 2.5 the web hole size respectively.